Terminologie e vocabolari Lessici specialistici e tesauri, glossari e dizionari - Grimaldi, Claudio; ZANOLA, Maria Teresa (Proceedings e report, 2021)
The volume contains the works selected by the Scientific Committee of the Italian Association for Terminology (Ass.I.Term), presented at the 2019 Annual Conference, hosted at the Accademia della Crusca. Italian lexicography has long been influenced by the masterpieces of literature, especially the oldest, and it is therefore in this perspective that the volume, which shows the vitality of studies in terminology, is inscribed, proposing a reflection that touches on the comparison between terminology and lexicography, through which technology and science can show their positive function for the development and growth of the Italian language.